AGE AND GROWTH IN THE CATFISH TACHYSURUS TENUISPINIS (DAY) - Dan, S S (Indian Journal of Fisheries, 2011)
Both the species of catfishes viz., T. tenuispinis and T. thdassirms formimportant fisheries along the Andhra, Orissa and West Bengal coasts contributingabout 20.8% of the demersal fish catches (Sekharan 1973a, & b).Maturity, fecundity and spawning (Dan 1976); length-weight relationship (Danand Mojumder 1975) and the food and feeding (Mojumder and Dan, MS) ofthe species have been studied. Pectoral spines in a few catfishes (Pantulu 1961,62) were used in the study of their age and growth. The present paper dealswith the study of age and growth with the help of opercular bones, otoliths andlengtii-frequency data in the catfish, T. tenuispinis.